(untitled) (Indian Journal of Arid Horticulture, 2021)
Recently phalsa is gaining popularity in arid and semi-arid regions due to drought tolerance, nutritional and medicinal value; and can be grown successfully in adverse climatic conditions of arid regions with limited supplemental irrigations and fertilizer application. Pruning is an essential cultural operation in phalsa for good flowering and fruiting. Therefore, present experiment was carried out during 2017 to 2019 to study the response of different pruning intensities and timings on vegetative growth, yield and quality attributes of phalsa ’CIAH-P-1’. The phalsa bushes were pruned on four dates viz., 30th November, 15th December, 30th December and 15th January at four intensities, i.e. 0.00 cm, 20 cm and 40 cm, and 60 cm height from ground level. It was observed that pruning timings and intensities had significant effect on sprouting period, bush height, number of twigs, number of fruiting clusters, number of fruits per cluster, fruits weight, total soluble solids and fruit yield per plant. Maximum average fruit yield (4.91 kg/plant), average fruit weight and diameter (1.14 g and 1.26 cm) and total soluble solids (25.02°Brix) were obtained when pruned the bushes at 20 cm from ground level on 15th of January, which was significantly higher from rest of the treatment combinations. On the findings of the study, it may be concluded that pruning in phalsa should be done on 15 to 20th of January at 20 cm height from ground level under Bikaner agro-climatic conditions of western Rajasthan.